Radiological characterisation of Petawatt laser interactions - Neely, D; Clarke, R; Brummitt, P; Collier, J; Danson, C; Edwards, C; Edwards, R; Frackiewicz, A; Govans, J; Hancock, S; Hatton, P; Hawkes, S; et al. (2004)
Vulcan is established as a world leading user facility for studies of ultra-high intensity laser interactions with matter. The Petawatt(PW) Upgrade project will deliver an order of magnitude increase in laser power to target, delivering interaction intensities of 10 21 Wcm -2. Before commencing operation to users a commissioning study was carried out. The objectives of this investigation were: To perform radiological surveys of the facility in anticipated target configurations and to install additional shielding for high-Z interactions as required To measure the target irradiance and the X-ray spot size To investigate the effects of electromagnetic noise on the chamber and target area equipment To determine the level of debris produced from the target and to devise a suitable operating scheme to protect chamber optics from damage Installation of an optical probe Contrast measurement of the laser pulses This report will review the experimental and radiological data obtained from the thirteen solid target interaction shots fired during the commissioning run in the newly constructed PW interaction facility 1) where doses of 45 mSv @ 1m were obtained. Commissioning of the PW laser and compressor chain is reported in separate articles, as is the commissioning of the large aperture gratings at high laser fluences 2).